Little red riding hood - Cloke, Rene (Nottinghamshire : Award publications limited, 2008)
Little Red Riding Hood is a story about a girl who goes to visit her sick grandmother. On the way, she meets a clever wolf who tricks her and gets to the grandmother$1 (Bs house first. The wolf dresses up as the grandmother to fool Little Red Riding Hood. In the end, a kind person saves them, and the girl learns to be careful with strangers.s
Location: 3D
Keywords: Fiction book